God's not dead [videorecording (DVD)] - Harper, Shane, 1993-; Cain, Dean; Sorbo, Kevin; White, David A. R. (Pure Flix Entertainment, 2014)
It's the debate of the ages; this time, held in a seemingly insignificant venue, but the outcome, as always, will be life-changing. A Christian college freshman, Josh Wheaton, and his atheist philosophy professor hold court on the existence of God. To pass the course, Josh must prove to the class that God is alive and well. This dare could cost him his relationships, his career, even his future, but Josh stands up for his faith and takes on the challenge.